2013
DOI: 10.1016/j.biosystemseng.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Cereal grain combustion in domestic boilers

Abstract: This study compared the combustion characteristics and the combustion behaviour of oats, barley, triticale and wheat to that of wood pellets. Sustained grain combustion in domestic boilers was feasible but problematic, the main impediment being clinker formation with ash agglomeration. Clinker formation was lowest for oats which burned easily with fewer operational problems. Triticale displayed reasonably good combustion characteristics and also ignited easily. In contrast, barley and wheat proved difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…NOx emissions when combusting cereal fuels have been noted to be high in the works of others. Keppel, et al [45] combusted oats and observed high NOx emissions of a similar magnitude to those seen here (630mg m -3 on a 6vol.% O2 basis), albeit their fuel had a higher fuel nitrogen content (1.8wt.%, as opposed to 1.1% for the oat hull waste fuel used here). With a wood fuel containing minimal fuel nitrogen content, Keppel, et al [45] saw NOx emissions around 20% of those produced with oats, a similar proportional difference as seen here between the white wood and oat hull waste.…”
Section: Emissionssupporting
confidence: 76%
See 1 more Smart Citation
“…NOx emissions when combusting cereal fuels have been noted to be high in the works of others. Keppel, et al [45] combusted oats and observed high NOx emissions of a similar magnitude to those seen here (630mg m -3 on a 6vol.% O2 basis), albeit their fuel had a higher fuel nitrogen content (1.8wt.%, as opposed to 1.1% for the oat hull waste fuel used here). With a wood fuel containing minimal fuel nitrogen content, Keppel, et al [45] saw NOx emissions around 20% of those produced with oats, a similar proportional difference as seen here between the white wood and oat hull waste.…”
Section: Emissionssupporting
confidence: 76%
“…Keppel, et al [45] combusted oats and observed high NOx emissions of a similar magnitude to those seen here (630mg m -3 on a 6vol.% O2 basis), albeit their fuel had a higher fuel nitrogen content (1.8wt.%, as opposed to 1.1% for the oat hull waste fuel used here). With a wood fuel containing minimal fuel nitrogen content, Keppel, et al [45] saw NOx emissions around 20% of those produced with oats, a similar proportional difference as seen here between the white wood and oat hull waste. This again highlights the importance of fuel nitrogen content and fuel NOx mechanisms for NOx formation at these sub-1000°C combustion temperatures.…”
Section: Emissionssupporting
confidence: 76%
“…On the other hand, Niedziółka et al [61] obtained comparable bulk density values for maize straw pellets (561-572 kg m −3 ). Higher values of bulk density were reported by Keppel et al [62] for various cereal and wood straw waste materials (520-718 kg•dm −3 ). Kirsten et al [59] also obtained high bulk density values (575-660 kg•dm −3 ) for hay pellets.…”
Section: Resultsmentioning
confidence: 58%
“…It was found that the durability of CG grain waste, and its mixtures with cobs and husks, was much lower compared to other materials and mixtures. The addition of CG reduced the durability of the pellets, which may be due to the chemical composition of this material and its physical properties, as well as mineral impurities, as indicated by other authors [51,54,62]. For further comparison of the obtained results with those of other works, mixtures with an undamaged grain base were considered.…”
Section: Resultsmentioning
confidence: 83%
“…After resourcing the food market, with the surplus of grain produced, stocks that have not been used for food purposes or are not suitable for human or animal consumption can be used for energy purposes for the production of biogas or direct combustion. Among cereals, oat (Avena sativa L.) has a special energetic value [32,37,38]. Avena sativa L. is an annual plant belonging to the Poaceae family.…”
Section: Introductionmentioning
confidence: 99%